1996
DOI: 10.1080/01688639608408305
|View full text |Cite
|
Sign up to set email alerts
|

Handedness and performance variability as factors influencing mirror movement occurrence

Abstract: A finger flexion task was used to investigate the effect of hand preference and performance variability on intensity of mirror movement. Right- and left-handed subjects were asked to maintain target forces, with either their index or small finger, that represented 25, 50, or 75% of their maximum strength capacity for the active finger. Greater mirror movement occurred when the small finger was active, and where there was greater variability in task performance, while mirror movement intensity was less when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
9
31
0
Order By: Relevance
“…Most previous studies that explored asymmetry of the physiological mirroring have reported that there was a stronger mirror activity during a voluntary movement of the nondominant hand. (Armatas et al 1994(Armatas et al , 1996Uttner et al 2007;Liederman and Foley 1987) Although the reverse pattern (Cernacek 1961) or no difference between the hands (Armatas and Summers 2001) has also been found. In our results, 17 out of the 20 participants who showed the ipsilateral activation just during left finger movement were right-handed.…”
Section: Discussionmentioning
confidence: 86%
“…Most previous studies that explored asymmetry of the physiological mirroring have reported that there was a stronger mirror activity during a voluntary movement of the nondominant hand. (Armatas et al 1994(Armatas et al , 1996Uttner et al 2007;Liederman and Foley 1987) Although the reverse pattern (Cernacek 1961) or no difference between the hands (Armatas and Summers 2001) has also been found. In our results, 17 out of the 20 participants who showed the ipsilateral activation just during left finger movement were right-handed.…”
Section: Discussionmentioning
confidence: 86%
“…Many studies reported that MMs or unaffected motor cortex activation can be changed or manipulated by exercise [30,37,38,39,40,41,42,43,44]. This suggests that MMs can be manipulated by rehabilitative management.…”
Section: Discussionmentioning
confidence: 99%
“…As intercortical effect could be crucial, debate as to whether laterality of the human hemisphere contributes to asymmetrical synkinesis invites researchersÕ attention. Many studies among healthy subjects have presented a greater amount or higher occurrence frequency of motor overflow when the non-dominant limb is active [5,12,38]. The invariant standpoint of GS asymmetry, however, was challenged by Parlow [30] who reported that synkinesis laterality depends primarily upon task characteristics.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the extent of GS asymmetry may depend on how GS is characterized. It is noteworthy that earlier studies of GS symmetry was based merely upon occurrence frequency of the homologous muscle [5,30], overlooking non-homologous irradiation coupled with synergistic movement of the whole nonexercised limb [17,43]. Besides, several factors that may influence GS characteristics have not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%